Striatal parvalbuminergic neurons are lost in Huntington's disease: implications for dystonia. Issue 12 (3rd September 2013) - Reiner, Anton; Shelby, Evan; Wang, Hongbing; DeMarch, Zena; Deng, Yunping; Guley, Natalie Hart; Hogg, Virginia; Roxburgh, Richard; Tippett, Lynette J.; Waldvogel, Henry J.; Faull, Richard L.M.
ABSTRACT Although dystonia represents a major source of motor disability in Huntington's disease (HD), its pathophysiology remains unknown. Because recent animal studies indicate that loss of parvalbuminergic (PARV+) striatal interneurons can cause dystonia, we investigated if loss of PARV+ striatal interneurons occurs during human HD progression, and thus might contribute to dystonia in HD. We used immunolabeling to detect PARV+ interneurons in fixed sections, and corrected for disease‐related striatal atrophy by expressing PARV+ interneuron counts in ratio to interneurons co‐containing somatostatin and neuropeptide Y (whose numbers are unaffected in HD). At all symptomatic HD grades, PARV+ interneurons were reduced to less than 26% of normal abundance in rostral caudate. In putamen rostral to the level of globus pallidus, loss of PARV+ interneurons was more gradual, not dropping off to less than 20% of control until grade 2. Loss of PARV+ interneurons was even more gradual in motor putamen at globus pallidus levels, with no loss at grade 1, and steady grade‐wise decline thereafter. A large decrease in striatal PARV+ interneurons, thus, occurs in HD with advancing disease grade, with regional variation in the loss per grade. Given the findings of animal studies and the grade‐wise loss of PARV+ striatal interneurons in motor striatum in parallel with the grade‐wise appearance and worsening of dystonia, our results raise the possibility that loss of PARV+ striatal interneurons is a contributor to dystonia in HD.